Answer:
4
Step-by-step explanation:
x=-6
Fill in for x
(-6)2/(-6)+3
-12/-3
=4
Answer: 381.7
Step by step explanation:
5 · (6 - 1) + 3
= 5·5 + 3
= 25 + 3
= 28
So for this trinomial, I will be factoring by grouping. Firstly, what two terms have a product of 16x^2 and a sum of 10x? That would be 8x and 2x. Replace 10x with 2x + 8x:
![x^2+2x+8x+16](https://tex.z-dn.net/?f=x%5E2%2B2x%2B8x%2B16)
Next, factor x^2 + 2x and 8x + 16 separately. Make sure that they have the same quantity inside the parentheses: ![x(x+2)+8(x+2)](https://tex.z-dn.net/?f=x%28x%2B2%29%2B8%28x%2B2%29)
<u>Now you can rewrite this as
, which is your final answer.</u>